Factors Affecting Sugarcane Supply in Panji and Wringin Anom Sugar Factories - Lawado, Nadhira Maulida Rizdanti; Aji, Joni Murti Mulyo (University of Jember, 2023)
Ensuring a harmonious match between the volume of sugarcane and the milling capacity is crucial for achieving an efficient production process. The yearly fluctuations in sugarcane supply depend on the consistency of the raw material and the adaptability of sugar factories to varying supply levels. This study aims to identify the factors that influence sugarcane supply, its uninterrupted flow, and its impact on revenue generation at the